French experience in environmental policy provision in the framework of the European Union (International relations and international law Journal, 2016)
Environmental issues and the protection of the environment is one of the key priorities of the EU. An extensive system of environmental laws, regulations, environmental principles, mechanisms and tools are formed and developing in the field and successfully implemented into the practice. Environmental policy is based on a unified approach to the organization of environmental protection measures, but each country has its own features. For example, in the United States and Canada, the main emphasis in environmental policy implementation is done on the system of laws, and in Western European countries, including France it focuses on the different programs, plans and recommendations. The article deals with the formation and development of environmental policy in France in the international and European context. Three key issues like the challenges, the institutions and the pollutions, have served as a guide for interdisciplinary research. The article focuses on the changes in these three fields.
Keywords: Environment; France; environmental policy; pollution; «Grenelle»